EVALUASI PEMBELAJARAN AKTIF KREATIF EFEKTIF DAN MENYENANGKAN DENGAN MODEL CONTEXT INPUT PROCESS PRODUCT - Gunadi, R. Andi Ahmad (Jurnal Ilmiah Widya, 2014)
Abstract: Active, creative, effective and fun learning is a learning model has been used in many kindergartens. This learning activity needs to be evaluated on its implementation. The purpose of this study is to evaluate the Active Learning Effective Creative and Fun with a model evaluation studies Context, Input, Process, Product: (1) Context, how is juridical bases and school proper study; (2) Input, how is the implementation of techniques of management, administration, learning schedule, facilities and infrastructures, (3) Process, how is the condition of teacher’s competency and learning process, (4) Products, how is learning objectives, students’ development achievement level and students competitiveness to continue to the next the level. The research used qualitative methods, conducted from March to December 2013 in the class B kindergarten Lab school Faculty of Education, University of Muhammadiyah Jakarta, which the number of respondents are 17 people. The results show that: (1) evaluation of context, juridical bases and proper study have met the standards stipulated on regulation, (2) evaluation of input, learning implementation has met the standards stipulated on government regulation; (3) evaluation of process, both teacher competence, good learning process; (4) evaluation of products, good value learning outcomes, level of student achievement progress well, the competitiveness of students to secondary school, either.